Secure Computing, Economy, and Trust: A Generic Solution for Secure Auctions with Real-World Applications - Bogetoft, Peter; Damgård, Ivan B.; Jakobsen, Thomas; Nielsen, Kurt; Pagter, Jakob; Toft, Tomas (BRICS Report Series, 2005)
In this paper we consider the problem of constructing secure auctions based on techniques from modern cryptography. We combine knowledge from economics, cryptography and security engineering and develop and implement secure auctions for practical real-world problems. In essence this paper is an overview of the research project SCET--Secure Computing, Economy, and Trust-- which attempts to build auctions for real applications using secure multiparty computation. The main contributions of this project are: A generic setup for secure evaluation of integer arithmetic including comparisons; general double auctions expressed by such operations; a real world double auction tailored to the complexity and performance of the basic primitives '+' and '<='; and finally evidence that our approach is practically feasible based on experiments with prototypes.